James Tobin and Modern Monetary Theory - Robert W. Dimand (Duke University, Center for the History of Political Economy (CHOPE), 2014)
This paper examines the relationship of the monetary economics of James Tobin to modern monetary theory, which has diverged in many ways from the directions taken by Tobin and his associates (for example, moving away from multi-asset models of financial market equilibrium and from monetary models of long-run economic growth) but which has also built upon aspects of his work (e.g., the use of simulation and calibration in his work on inter-termporal consumption decisions). Particular attention will be paid to Tobin's unpublished series of three Gaston Eyskens Lectures at Leuven on Neo-Keynesian Monetary Theory: A Restatement and Defense, and the paper draws on my forthcoming volume of Tobin for Palgrave Macmillan's series on Great Thinkers in Economics.
Keywords: B22; B31; E12; 330; James Tobin; modern monetary theory; microeconomic foundations; Keynesian economics; corridor of stability